1999
DOI: 10.1002/(sici)1521-4109(199904)11:4<223::aid-elan223>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

The Technology of Hot-Wire Electrochemistry

Abstract: The technologic basis for in situ heating of a microelectrode wire by high amplitude, high frequency alternating current (hot-wire electrochemistry) is presented. The preferred modes are continuous heating until a stationary temperature value is established, and pulsed heating with short time current sampling. The latter allows measurement above the boiling point.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…In every case, as mandatory to all versions of hot-wire electrochemical experiments, electrodes are arranged symmetrically, with an electrical connection to the working electrode terminal of a potentiostat [1]. In every case, as mandatory to all versions of hot-wire electrochemical experiments, electrodes are arranged symmetrically, with an electrical connection to the working electrode terminal of a potentiostat [1].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In every case, as mandatory to all versions of hot-wire electrochemical experiments, electrodes are arranged symmetrically, with an electrical connection to the working electrode terminal of a potentiostat [1]. In every case, as mandatory to all versions of hot-wire electrochemical experiments, electrodes are arranged symmetrically, with an electrical connection to the working electrode terminal of a potentiostat [1].…”
Section: Methodsmentioning
confidence: 99%
“…According to (1), every value of superheat DW in Kelvin is related to a bubble with de®nite value of r in [m] on the surface, that is in equilibrium with the liquid under this set of conditions [4]. If we consider a homogeneous liquid region surrounding the electrode, we can claim that it should be possible to keep this region homogeneous until supercritical temperatures are reached, if bubble nucleation doesn't occur during the fast temperature rise.…”
Section: Introductionmentioning
confidence: 99%
“…One example is voltammetry with in situ generation of temperature variations. This field of research was predominantly influenced by contributions from Gründler's group [3]. On the basis of microwire electrodes heated by AC currents it was demonstrated that local temperature control at microelectrode surfaces can be an effective means to enhance the analytical performance of voltammetric measurements.…”
Section: Voltammetric Electrodes and Cell Configurationsmentioning
confidence: 99%
“…Grü ndler and coworkers [12,13] have studied and demonstrated the application of hot wire electrodes. Radio-frequency heating has been applied to macroelectrodes in flow cell systems [14,15] and has been shown by Baranski [16] to allow high temperature conditions to be applied at conventional microelectrodes.…”
Section: Introductionmentioning
confidence: 99%